Comparative Analysis of the Tax Structures of Bulgaria, Denmark and France - Martina, Yakova D. (International Journal of Economics and Financial Issues, 2017)
The survey analyzes the type of tax structure and the link with economic growth. The tax revenue types of Bulgaria, Denmark and France were investigated under a different tax structure. The survey covers countries with different tax structures, incl. Income, Consumer, and Hybrid (Mixed). The choice of countries surveyed results from the fact that they generate revenue in the budget as a ratio between direct and indirect taxes in a different way. For the empirical analysis, a linear regression model was used in the form of the Least Squares Method (LSM). On this basis, the state's redistributive function was assessed as a burden of taxation. Keywords: Taxes; Tax structure; Economic growth; Government expenditure JEL Classifications: H24; H25; H63